The relationship between relative rest and team performance across competitive seasons in the National Football League - Pinzone, A. G.; Abu-Amara, Y.; Gant, R. W.; Rivera, J.; Tagesen, E. C.; Barkley, J. E.; Jajtner, A. R. (The Journal of Strength and Conditioning Research, 2025)
This investigation aimed to assess the relationship between relative rest index (RRI) and team performance across multiple seasons of National Football League (NFL) competition. To examine this relationship, all NFL regular season games from the 1970-71 to 2022-23 NFL seasons (N = 12,290) were analyzed with rest intervals calculated for each team on a game-to-game basis as the number of days between current and previous games. Next, RRI was calculated as the discrepancy in rest intervals between competing teams for all games and averaged for all teams across all seasons with teams categorized by season average RRI (<-0.70; -0.7 to -0.5; -0.5 to -0.25; -0.25 to 0; 0 to 0.25; 0.25 to 0.5; 0.5 to 0.7; >0.70). Win percentage and playoff depth (lost in wild card round; lost in divisional round; lost in conference championship; lost in Super Bowl; won Super Bowl; did not make playoffs) quantified team performance. Pearson product correlations were implemented to assess the relationship between season average RRI and win percentage. One-way analyses of variance assessed differences in win percentage across RRI categories and RRI across playoff depth categories. A trivial negative correlation between RRI and win percentage across all seasons was noted. Moreover, win percentage did not differ across RRI categories, while RRI was attenuated among teams that lost in the Super Bowl and divisional round compared with teams that did not qualify for the playoffs, suggesting that RRI has no significant effect on team performance with competitive eras of NFL competition collated.